2018
DOI: 10.1016/j.bbr.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Amygdaloid involvement in the defensive behavior of mice exposed to the open elevated plus-maze

Abstract: Previous studies have shown that the exposure to an open elevated plus maze (oEPM, an EPM with all four open arms) elicits fear/anxiety-related responses in laboratory rodents. However, very little is known about the underlying neural substrates of these defensive behaviors. Accordingly, the present study investigated the effects of chemical inactivation of the amygdala [through local injection of cobalt chloride (CoCl: a nonspecific synaptic blocker)] on the behavior of oEPM-exposed mice. In a second experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In addition to the lateral hypothalamus [37], the posterior hypothalamus may be involved in RA (in the form of novel object exploration) and may concurrently control the anxiety-related neuroendocrine stress response [38]. Consistent with the top-down control of the PAG by the amygdala in relation to freezing and flight, the basolateral amygdala appears to be involved in the generation of RA as measured by stretch-attend in the elevated plus-maze [39] and by the firing of one group of its cells during periods of hesitation or retreat, but not of escape [40*].…”
Section: Subcortical Risk Assessment Survival Circuitsmentioning
confidence: 86%
“…In addition to the lateral hypothalamus [37], the posterior hypothalamus may be involved in RA (in the form of novel object exploration) and may concurrently control the anxiety-related neuroendocrine stress response [38]. Consistent with the top-down control of the PAG by the amygdala in relation to freezing and flight, the basolateral amygdala appears to be involved in the generation of RA as measured by stretch-attend in the elevated plus-maze [39] and by the firing of one group of its cells during periods of hesitation or retreat, but not of escape [40*].…”
Section: Subcortical Risk Assessment Survival Circuitsmentioning
confidence: 86%
“…In addition, in the present study, we showed that male animals presented a lower numbers of PHD and higher NPHD movements in relation to female (at the same age), indicating an effect of gender in these parameters. This result can be related to an increase in both exploratory behavior and risk assessment, as well as a decrease in anxiety‐like behaviors (Sorregotti et al, 2018). In contrast, female rats showed lower latency time to start exploring the apparatus, and there was an interaction between gender and maternal deprivation on the rearing behavior at P42.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the neuropharmacological basis of altered open-arm avoidance of inbred mouse strains using the EPM, report a consistent dose-dependent anxiolytic effect of systemically administered benzodiazepines ( Rodgers et al, 1992; Cole and Rodgers, 1995; Holmes and Rodgers, 1999; Griebel et al, 2000 ) which emphasizes the predictive validity of this testing situation. More recent studies which assess the involvement of specific brain areas in the expression and regulation of open-arm avoidance in rats and mice implicate the prefrontal cortex (PFC) ( Adhikari et al, 2010,2011; Kumar etal., 2013 ), bed nucleus of the stria terminalis(BNST) ( Kim etal., 2013 ), lateral septum (LS) to anterior hypothalamic area (AHA) projection ( Anthony et al, 2014 ), medial septum (MS) ( Shin et al, 2009; Zhang et al, 2017 ), septo-habenular pathway ( Yamaguchi et al, 2013 ), basolateral amygdala (BLA) ( Sorregotti et al, 2018 ) and specifically its projections towards the central nucleus of the amygdala (CeA) ( Tye et al, 2011 ) and ventral hippocampus (vHPC) ( Felix-Ortiz et al, 2013 ) and PFC ( Felix-Ortiz et al, 2016 ), vHPC to PFC projection ( Padilla-Coreano et al, 2016 ), vHPC-lateral hypothalamic area (LHA) projection ( Jimenez et al, 2018 ), habenula (Hb) ( Pang et al, 2016 ), interpeduncular nucleus (IPN) ( Zhao-Shea et al, 2015 ), laterodorsal tegmentum (LdT) ( Yang et al, 2016 ) but also the PAG ( Santos et al, 2003; Netto and Guimarães, 2004; Borelli and Brandão, 2008; Lima et al, 2008; Campos and Guimarães, 2009; Mendes-Gomes and Nunes-de Souza, 2009; Terzian et al, 2009; Muthuraju et al, 2016 ) and the SC ( Muthuraju et al, 2016 ). It is clear that all these brain structures cannot mediate the same types and aspects of avoidance behavior (e.g.…”
Section: Discussionmentioning
confidence: 99%